2005
DOI: 10.1121/1.1904405
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic particle concentration in a line-driven cylindrical tube

Abstract: Acoustic particle manipulation has many potential uses in flow cytometry and microfluidic array applications. Currently, most ultrasonic particle positioning devices utilize a quasi-one-dimensional geometry to set up the positioning field. A transducer fit with a quarter-wave matching layer, locally drives a cavity of width one-half wavelength. Particles within the cavity experience a time-averaged drift force that transports them to a nodal position. Present research investigates an acoustic particle-position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 33 publications
3
68
0
Order By: Relevance
“…This hydrodynamic focusing results from several stability developments (Steen 1990), and is used in most flow cytometers. However, other focus concepts exist, such as microcapillary technology or acoustic focusing (Ward et al 2009) which allows alignment of cells by sound waves (Goddard et al 2006(Goddard et al , 2007Goddard and Kaduchak 2005) without damage to cells (as ultrasound for fetus in utero medical exam).…”
Section: Flow Cytometry Fundamentalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This hydrodynamic focusing results from several stability developments (Steen 1990), and is used in most flow cytometers. However, other focus concepts exist, such as microcapillary technology or acoustic focusing (Ward et al 2009) which allows alignment of cells by sound waves (Goddard et al 2006(Goddard et al , 2007Goddard and Kaduchak 2005) without damage to cells (as ultrasound for fetus in utero medical exam).…”
Section: Flow Cytometry Fundamentalsmentioning
confidence: 99%
“…Since 2010, Life technologies TM Corporation proposes an acoustic focusing analyzer that uses sound waves to precisely control cell movement (Goddard and Kaduchak 2005;Goddard et al 2006Goddard et al , 2007. Attune TM equipped with a 50 mW 405 nm and 20 mW 488 nm solid-state lasers, analyzes FSC, SSC and six colors.…”
Section: Attune Tm (Applied Biosystems Tm By Life Technologies Tm )mentioning
confidence: 99%
“…Goddard and Kaduchak (2005) demonstrated a method for concentrating particles along a single line through precise control of the acoustic wave in a small cylindrical tube, reminiscent of the work by Vainshtein et al (1996) some 10 years prior, and representative of the many ideas for particle manipulation appearing in the literature in combination with microfluidics. As one of the earliest combinations of acoustic energy and microfluidics for manipulating particles in a closed system known to us, Kaajakari et al (2001) made a broad-based attempt to mix and pump fluids and manipulate suspended particles within.…”
Section: In Closed Environmentsmentioning
confidence: 99%
“…A relatively early study by Kumar et al (2005) reported the acoustic separation of hybridoma and lactobacillus using ultrasound irradiation perpendicular to the main axis of flow, with modest efficiency and flow rate. Goddard and Kaduchak (2005) used ultrasound to focus 10 m particles and cells in a 190 mm long glass capillary tube with an inner diameter of 1.9 mm along a 14 mm long region exposed to acoustic radiation at 417 kHz from a pair of PZT transducers attached to either side of the tube. They were able to focus the objects to within a 40 m region at the center of the flow using this configuration with nearly 100% concentration efficiency.…”
Section: In Closed Environmentsmentioning
confidence: 99%
“…44,45 Based on this functioning principle, concentration of a range of particles including bacterial spores, biological cells and polystyrene spherical micro-beads has been demonstrated. 15,38,[46][47][48][49][50][51] Nordin and Laurell have recently demonstrated a very significant increase in concentration of red blood cells and prostate cancer cells (up to a maximum of ~200-fold), using a two-stages half-wavelength resonator. 15 However, direct manipulation of bodies as small as bacteria by means of ARFs represents a considerable physical challenge.…”
Section: Introductionmentioning
confidence: 99%